Upaya Konselor Adiksi dalam Mengatasi Kejenuhan Residance Pecandu NAPZA - Rantekata, Nurul Ahwat; Nurjannah, Nurjannah (Palita: Journal of Social Religion Research, 2022)
The rehabilitation program is one of the ways taken as a curative effort in overcoming drug addiction. Residance undergoing a rehabilitation program cannot be separated from various comprehensive problems that can possibly interfere with the residance recovery process during the rehabilitation program. The purpose of this study is to find out what are the factors that cause drug addict recidance saturation and how the efforts made by the addiction counselors in overcoming drug addict residance saturation. This research is considered as a type of descriptive qualitative research. The data collection technique in this study used purposive sampling techniques which taken the sample of the data or informant from an addiction and residance counselor who experienced saturation during the rehabilitation program. The data collection technique in this study used interviews, observations and documentation. Meanwhile, data analysis techniques use interactive analysis techniques from Miles Huberman, which are data reduction, data presentation, and drawing conclusions. The results of this study revealed that the factors caused recidance to experience saturation are due to less productive residance during the rehabilitation program, irregular lifestyle and feelings of spiritual emptiness. Meanwhile, the efforts made by the addiction counselor in dealing with recidance saturation are to conduct counseling and provide motivation to the recidance so that they can draw closer to Almighty God that can increase the spritual residance. The addiction coun’elor's efforts made during the rehabilitation process have been proven to be able to overcome the boredom experienced by drug addict residance.